Self-organizing Approach for Real-time Data Fusion in Dense Wireless Sensor Networks - Alex Sandro Roschildt Pinto (2009)
Wireless Sensor Networks (WSN) are usually composed for a huge number of tiny nodes deployed in an environment that has to be monitored. Due to high probability of faults in communication level and in the nodes itself, network topology becomes very dynamic and unpredictable. Several challenges are faced in these networks like real-time and quality of service. Moreover, it is very difficult to fix the network due to environmental issues or the huge number of nodes. This way self-organizing and self-organizing approaches are required to maintain the network services. In this paper a selforganizing approach for real-time data fusion applications is presented. Our approach showed that is possible to achieve the required levels of communication efficiency or quality of service required by system administrators.